Medical complications among type 2 diabetes mellitus patients at a general hospital in East Coast Malaysia - M, Noor Hasimah; MN, Nurhanani; Musa, Ramli (Faculty of Medicine, International Islamic University Malaysia, 2010)
Introduction: Diabetes Mellitus (DM) is a chronic metabolite disorder with high potential of multisystemic medical complications especially among poorly controlled patients. This study was conducted at Raja Perempuan Zainab II Hospital, Kota Bharu with objectives to explore the pattern of common diabetic mellitus type 2 complications and to compare between gender and races in relation to other risk factors during their hospitalization. Materials and Methods: This is a retrospective study based on atients’ record involving 215 patients (110 women and 105 men) who were admitted with diabetic complications in medical ward for a period of 6 months (January to June 2006) Results: Out of total 300 identifi ed subjects, 285 case notes were traceable. From 285, 84.6% (241 subjects) were diagnosed as DM type 2. 215 out of 241 subjects (89.2%) had one or more diabetic complications. In general the most common diabetic complication was diabetic nephropathy 34.9% (75 patients). When we compared between genders, diabetic foot ulcers was the most common diabetic complications among males (43.8%) and diabetic nephropathy for females (40.9%). A total of 199 patients (92.6%) had poor blood sugar control during their hospitalization and 103 patients (47.9%) had hypertension. Conclusion: Patients with DM type 2 had a high prevalence of complications. Common diabetic complications among genders were varied. Patients with diabetic complications had high prevalence of risk factors such as poor blood sugar control, concomitant hypertension and smoking habit.